Correlation between preoperative CT imaging parameters and clinical outcome of lumbar spinal stenosis treated with endoscopic transforaminal decompression. Issue 4 (April 2020) - Li, Lijun; Hai, Yong; Yang, Jincai; Xu, Cheng; Yuan, Jie; Sun, Jiuqiang; Wang, Qinghua; Yang, Xiaowen
Objective: To evaluate clinical effects, and their correlations with preoperative computed tomography imaging parameters, in cases of lumbar spinal stenosis treated by endoscopic transforaminal decompression. Methods: This retrospective study included orthopaedic patients who had undergone percutaneous endoscopic lumbar discectomy (PELD) for lumbar spinal stenosis. Clinical symptoms were evaluated by visual analogue scale (VAS), Oswestry Disability Index (ODI) and claudication distance. Overall clinical efficacy was evaluated by Macnab score. Results: A total of 87 patients were included. Postoperative wound healing was good without complications. Macnab scores following PELD were 'excellent' in 41 cases (47.12%), 'good' in 30 cases (34.48%), 'generally good' in seven cases (8.04%), and 'poor' in nine cases (10.34%). The overall rate of optimal surgery was 81.60%. Postoperative pain (VAS) and ODI scores, and claudication distance, were significantly improved versus preoperative values. The soft tissue invasion ratio of the vertebral canal and invasion ratio of the nerve root canal were correlated with clinical efficacy. Conclusion: Positive correlations were observed between clinical efficacy of endoscopic transforaminal decompression and preoperative vertebral canal soft tissue invasion ratio and nerve root canal invasion ratio in patients with lumbar spinal stenosis.